Olive oil and clove oil-based nanoemulsion for topical delivery of terbinafine hydrochloride: in vitro and ex vivo evaluation - Uzma Gul; Muhammad Imran Khan; Asadullah Madni; Muhammad Farhan Sohail; Mubashar Rehman; Akhtar Rasul; Leena Peltonen (Taylor & Francis Group, 2022)
In this article, formulation studies for terbinafine hydrochloride nanoemulsions, prepared by high-energy ultrasonication technique, are described. Pseudo-ternary phase diagram was constructed in order to find out the optimal ratios of oil and surfactant/co-solvent mixture for nanoemulsion production. Clove and olive oils were selected as oil phase. Based on the droplet size evaluation, maximum nanoemulsion region were determined for formulation development. Further characterization included polydispersity index (PDI), zeta potential, Fourier transform infrared (FT-IR) spectroscopy, morphology, pH, viscosity, refractive index, ex vivo skin permeation, skin irritation, and histopathological examination. Droplet sizes of optimized formulations were in colloidal range. PDI values below 0.35 indicated considerably homogeneous nanoemulsions. Zeta potential values were from 13.2 to 18.1 mV indicating good stability, which was also confirmed by dispersion stability studies. Ex vivo permeation studies revealed almost total skin permeation of terbinafine hydrochloride from the nanoemulsions (96-98%) in 6 hours whereas commercial product reached only 57% permeation at the same time. Maximum drug amounts were seen in epidermis and dermis layers. Skin irritation and histopathological examination demonstrated dermatologically safe formulations. In conclusion, olive oil and clove oil-based nanoemulsion systems have potential to serve as promising carriers for topical terbinafine hydrochloride delivery.